Autonomous Intelligence : A Technical Analysis of Self-Directing AI Systems and Their Enterprise Implementation - Naresh Babu Goolla (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the emerging landscape of autonomous AI agents and personalized assistants, examining how technologies like AutoGPT and BabyAGI are revolutionizing AI system independence through multi-step task execution capabilities. The article delves into the technical foundations enabling these systems to operate with increased autonomy while maintaining relevance to user needs. A comprehensive article on personalized AI assistants, including OpenAI’s Custom GPTs and Meta’s AI assistants, reveals their advanced context retention abilities and recommendation systems. The discussion encompasses implementation strategies for enterprise adoption, technical integration considerations, and these technologies’ strategic implications for business transformation. The article concludes with insights into the evolving relationship between humans and increasingly autonomous AI systems, highlighting both challenges and opportunities in this rapidly advancing field.